The Development of Mountain Tourism in Zamin District - Bobur-Mirzo, Berdimurodov (International Journal on Integrated Education, 2023)
Zamin District, with its majestic mountains and untamed wilderness, holds great promise for the development of mountain tourism. This article explores the opportunities, challenges, and strategies involved in harnessing the full potential of mountain tourism in Zamin District. By capitalizing on its natural assets, preserving its cultural heritage, and fostering community engagement, Zamin District can establish itself as a premier destination for adventure enthusiasts, nature lovers, and cultural explorers. This article delves into key aspects such as infrastructure development, environmental conservation, community participation, and effective marketing initiatives required to unlock the untapped potential of mountain tourism in Zamin District.